If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + 3) = -4(2y + -6) + 3y Reorder the terms: 4(3 + y) = -4(2y + -6) + 3y (3 * 4 + y * 4) = -4(2y + -6) + 3y (12 + 4y) = -4(2y + -6) + 3y Reorder the terms: 12 + 4y = -4(-6 + 2y) + 3y 12 + 4y = (-6 * -4 + 2y * -4) + 3y 12 + 4y = (24 + -8y) + 3y Combine like terms: -8y + 3y = -5y 12 + 4y = 24 + -5y Solving 12 + 4y = 24 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. 12 + 4y + 5y = 24 + -5y + 5y Combine like terms: 4y + 5y = 9y 12 + 9y = 24 + -5y + 5y Combine like terms: -5y + 5y = 0 12 + 9y = 24 + 0 12 + 9y = 24 Add '-12' to each side of the equation. 12 + -12 + 9y = 24 + -12 Combine like terms: 12 + -12 = 0 0 + 9y = 24 + -12 9y = 24 + -12 Combine like terms: 24 + -12 = 12 9y = 12 Divide each side by '9'. y = 1.333333333 Simplifying y = 1.333333333
| 4x-9x+4=x-3+7 | | 3a=6-a | | sqrt(x)+4y=65 | | 2.5z=250 | | x+-3=2x | | 2(a-2rt)=4r-6s | | 8k^2/32k | | 12a-744=46 | | 7z+2=9-3 | | 2c+12+c=51 | | 6+-4x=2x | | 3-(6x-2)= | | 3(5x+6)-4(x+3)= | | n/1.2=1.8 | | 2x+3y-5x-5y= | | px+Q=14x-23 | | y=-14x+9 | | -3(-6y+9)-5y=7(y-2)-3 | | 15y^2-50y+35= | | c/35=23 | | 22p+9=-8t-13 | | b/7.5=2.8 | | 8y=5x-120 | | 6p^2-32p+5= | | 2X^4-12X^3-16X^2=0 | | 6+2(3u-4)=-3(5u-2)+3u | | 12x+2-3=10-(x-3) | | 2(2m-5)-4= | | d/54=1.83 | | 15x+25x=20x | | 627+12=9x | | 4d+9=24 |